Fabrication of a MEMS micromirror based on bulk silicon micromachining combined with grayscale lithography - Garcia, Ines S. (2020)
A 1D MEMS (Micro-Electro-Mechanical Systems) mirror for LiDAR applications, based on vertically asymmetric comb-drive electrostatic actuators, is presented in this work employing a novel fabrication process. This novel micromachining process combines typical SOI-based bulk micromachining and grayscale lithography, enabling the fabrication of combs actuators with asymmetric heights using a single lithography step in the active layer. With this technique, the fabrication process is simplified, and the overall costs are reduced since the number of required lithography steps decrease. The fabricated mirrors present self-aligned electrodes with a 2.8 mu m gap and asymmetric heights of the movable and the fixed electrodes of 20 mu m and 50 mu m, respectively. These asymmetric actuators are an essential feature for the operation mode of this device, enabling both in resonant and static mode operation. A mirror field of view (FOV) of 54 degrees at 838 Hz was achieved under low-pressure, when resonantly operated, and a FOV of 0.8 degrees in the static mode.